Analisis Senyawa Fenolat Dan Uji Aktivitas Antioksidan Buah Markisa (Passiflora Edulis Sims) Secara Spektrofotometri Visibel - Fithriani Armin; Ermadanis Ermadanis; Roslinda Rasyid (STIFARM Padang, 2014)
Has done research on the analysis of phenolic compounds and antioxidant activity test on passion fruit (Passiflora edulis Sims) by visible spectrophotometry method. To determine the presence of phenolic compounds in the sample to be identified with iron (III) chloride is characterized by the formation of dark blue color on the sample. Samples were macerated with 96% ethanol, performed three repetitions and the filtrate was concentrated using a rotary evaporator at a temperature of 400 C. Extracts were obtained determined the levels of phenolic compounds using Folin-ciocalteau method and test the antioxidant activity using DPPH method. Standard solution used is gallic acid. Equation linearity gallic acid used in the determination of phenolic compounds in the sample is y = 0.004x + 0.1366 with correlation coefficient (r) = 0.9956 measured at λ max 761.5 nm. the levels of phenolic compounds were obtained on average at the sample was 0.0377% w / w. The average percent inhibition of passion fruit sample solution were counted against the maximum wavelength of 512.0 nm DPPH is 19.8763%. The antioxidant activity of the sample solution of 10 mg is equivalent to 618.9760 mg gallic acid and gallic acid solution IC50 of 1.5604 mg / mL of the sample solution while the IC50 14.4751 mg / mL.